The Law of Loans in Meeting the Needs of Marriage from the Perspective of Islamic Fiqh - Affandi, Ahmad Zulkifli; Satrianingsih, Andi; Asdar, A (Journal of Family Law and Islamic Court, 2023)
Marriage in Islam as worship, follows the Sunnah of the Prophet. In modern society, high costs drive the Marriage in Islam as worship follows the Sunnah of the Prophet. In modern society, high costs drive the demand for loans, to be considered according to the principles of Islamic jurisprudence. This research explores the law of lending for marriage needs in the perspective of Islamic jurisprudence, focusing on financial solutions for new couples. Qualitative research methods with data sources from libraries, online databases, official websites of religious organizations, and electronic journals. The results showed that in the perspective of Islamic jurisprudence, taking a loan for marriage is permissible on the condition of good faith, emergency, and the ability to pay off debts. The views of scholars vary, but the main principle is to maintain chastity and build an Islamic family by avoiding usury. The implementation of loan law emphasizes clear agreements and intentions, without interest or usury, as well as transparency of terms and conditions. Good intentions, halal fulfillment, ability to pay back, and fairness in transactions are key. Maintaining these principles ensures community involvement in lending that adheres to Islamic values, supports financial policies that are in accordance with Islamic ethics and morals, provides long-term benefits to Islamic families and communities. In conclusion, marriage loans in Islamic jurisprudence are permissible on condition of good faith, emergency, and ability to repay. Implementation requires agreement and clear intentions, no interest, upholding Islamic values, and ensuring long-term benefits for Islamic families and communities